Biological markers of disease activity in inflammatory bowel diseases - Edyta Szymanska; Sylwia Szymanska; Maciej Dadalski; Jaroslaw Kierkus (Gastroenterology Review)
Inflammatory bowel diseases (IBD) are chronic intestinal conditions of multifactorial aetiology including genetic susceptibility, immunological impairment, dysbiosis, and environmental factors. The diagnosis is based on both clinical and endoscopic features, wherein histopathological evaluation remains a gold diagnostic standard. However, fast, reliable, and non-invasive biological markers have been used for years for diagnosis as well as for disease activity monitoring. Currently, commonly used faecal calprotectin is the only biomarker approved and recommended by the European Crohn’s and Colitis Organization (ECCO). Nonetheless, other biological markers discriminating between functional and organic bowel conditions have been widely studied. Therefore, the aim of this manuscript was to review new potential biomarkers of inflammation in IBD. The aim of this study was to review currently available biomarkers of intestinal inflammation and increased gut permeability in IBD.